Factores psicosociales asociados a la depresión en los adultos mayores, que habitan en la parroquia Julio Moreno del cantón Guaranda provincia Bolívar durante el período diciembre 2018-mayo 2019 - Veloz Peñaherrera, Katherine Mishel (2019)
The research was carried out in order to determine the psychosocial factors associated with depression in older adults, Julio Moreno Parish, by identifying the sociodemographic profile and describing the psychosocial factors associated with the problem, in addition to proposing a didactic guide for the management and care of depression. The quantitative and qualitative research, in which 30 people defined as the sample of the research were analyzed; in which a survey with defined variables was applied; in addition to carrying out the geriatric test Yesavage constituted by 15 items in order to determine a possible depression. From the results obtained it has been determined that the population of older adults in around 90% have all the essential basic services, however, their mood reflects a depression in mild conditions, in addition, the psychosocial factors associated with the problem determined were to a greater degree the social abandonment that includes authorities and community in general, also, the self-perception of health is identified in 80% as a state in poor conditions. In this way it is recommended to follow up as an element of social and family responsibility, since from the academic part it is contributed with a manual oriented to the depression; the same one that will contribute to the care and handling in relatives and professionals of the health, that interact with the patient.